Analisis Hubungan Antara Disiplin Kerja, Kepemimpinan Dan Penghargaan Dengan Kinerja Perawat Dalam Pendokumentasian Asuhan Keperawatan di RSUD Poso - Deiby, M. M. Sigilipu; Jeanette I. C. Manoppo; Erling D. Kaunang (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2025)
Nursing care documentation is an important part of quality nursing services. However, the quality of documentation in various health facilities, including RSUD Poso, is still low. This study analyses the relationship between work discipline, leadership, and rewards with nurses' performance in documenting nursing care in the inpatient ward of RSUD Poso. Using a cross sectional analytic design, data were obtained through questionnaires from 62 nurses and analysed with chi-square test and prevalence ratio using SPSS 25. Results showed 77.4% of nurses had good documentation performance. There was a significant relationship between leadership (p=0.006; PR=5.400), appreciation (p=0.000; PR=26.000), and work discipline (p=0.010; PR=4.846) with nurse performance. Nurses who receive effective leadership, appropriate rewards, and have high work discipline tend to have better documentation performance. The study recommends that hospital management strengthen participative leadership, provide appropriate rewards, and foster a culture of discipline to improve documentation quality and patient safety.